Removal of Heavy Metal Ions using Amine-Functionalized Mesoporous Adsorbent - Teh , Weng Kean (IRC, 2016)
The capability of adsorption of heavy metals such as Cu (II) and Cr (VI) ions from an aqueous solution using amine-functionalized MCM-41 mesoporous silica was investigated in this study. In the present work, 20% of secondary and tertiary amine functional groups namely, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AAPTMS) and 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane (AEPTMS) were loaded into MCM-41, respectively, via co-condensation synthesis method. The structure and properties of the amine-functionalized MCM-41 absorbents were characterized by Fourier transform infrared (FT-IR) spectrometry and scanning electron microscope (SEM).